“PEMANFAATAN LIMBAH RUMAH TANGGA DAN LIMBAH PERTANIAN SEBAGAI PUPUK ORGANIK DI DESA GEKBRONG CIANJUR” - Hadayanti, Didit (Universitas Al Ghifari, 2023)
ABSTRACTThe waste problem that is generally emerging is dominated by urban areas with limited landfill space, resulting in not only environmental pollution but also health impacts. One example is Cianjur Regency, which is one of the contributors to waste. Currently, Cianjur Regency is experiencing a waste crisis due to the Pasir Sembung landfill being overloaded with waste, prompting the Cianjur Regency Government to move the landfill to Mekarsari. The increasing population in Cianjur leads to an increase in the volume of waste generated, including household, industrial, and commercial waste. Many areas in Cianjur still lack efficient waste management systems. Landfills are often full and unable to accommodate the continuously growing waste. Kampung Loji, in the Gekbrong sub-district of Cianjur Regency, faces issues related to the large amount of organic waste, causing waste to pile up at the landfill. The goal of this KKN (Student Community Service) activity is to raise community awareness in reducing the accumulation of organic waste and to create a clean environment. The method used is providing education on the utilization of household and agricultural waste into organic fertilizer to the community. The results of this KKN activity help the community reduce the problem of organic waste, which has been managed well by utilizing organic waste, thereby providing added value to the community. Keywords: KKN Unfari Bandung, Gekbrong Village, Organic Wast.